Participation of Bussiness Actors in Conservation Activity at Gunung Tangkuban Perahu Nature Tourism Park: PARTISIPASI PELAKU USAHA DALAM KEGIATAN KONSERVASI DI TAMAN WISATA ALAM GUNUNG TANGKUBAN PERAHU - Hasanah, Siti; Sunkar, Arzyana; Ekayani, Meti (Media Konservasi, 2019)
Participation of community as business actors in Gunung Tangkuban Perahu Nature Tourism Park (GTPNTP) is a key to sustainable management of conservation areas through conservation activities. Conservation activities in GTPNTP have not been maximized, so needs to support by various stakeholders. This study aims to determine the level of participation of business actors in conservation activities in GTPNTP by studying economic benefits obtained by business actors from tourism activities through their willingness to contribute for conservation activities and their willingness to pay for conservation funds. The methods used were observation, quetionnaire, interview, and literature study. Respondent amount of 58 business actors using stratified random sampling technique. The results showed that in general, business actors get economic benefits from tourism revenues with a high contribution to the share (78,59%) and very high to the covering (120,46%). Most of the participation levels of business actors included in the very low category by 88,33% and the low category by 11,67%. In general, business actors have contributed to conservation activities in GTPNTP and 60% are willing to pay for conservation funds. This study shows that the willingness of business actors to contribute for conservation activities is quite high. Keywords: business actors, conservation activities, economic benefits, Gunung Tangkuban Perahu Nature Tourist Park, participation